Exploring Correlates of Loss of Control Eating in a Nonclinical Sample - Conceição, Eva M.; Moreira, Célia S.; de Lourdes, Marta; Ramalho, Sofia; Vaz, Ana Rita (Frontiers in Psychology, 2022)
Objective Loss of control (LOC) eating has been directly related to the core aspects of the psychopathology of eating disorders and to different dimensions of emotion and behavior regulation and self-criticism. This study investigates a model representing the interplay between these dimensions to understand LOC eating among a nonclinical sample. Methods A total of 341 participants, recruited in a college campus (mean age 23.21, SD = 6.02), completed a set of self-report measures assessing LOC eating, weight suppression, psychopathology of eating disorders, depression, negative urgency, emotion regulation difficulties, and self-criticism. Path analysis modeling tested a hypothesized model with 3 paths for LOC eating as follows: (1) psychopathology of eating disorders; (2) emotion and behavior regulation; and (3) interplay between these paths. Results We found goodness-of-fit indexes to our data: χ2 = 17.11, df = 10, Comparative Fit Index (CFI) = 0.99, Tucker-Lewis index (TLI) = 0.98, Root Mean Square Error Approximation (RMSEA) = 0.045, Standardized Root Mean Square Residual (SRMR) = 0.041, suggesting that: (1) participants with higher weight suppression showed higher degrees of the psychopathology of eating disorders, which was linked to higher levels of LOC eating; (2) self-criticism was a mediator between emotion regulation and depression/negative urgency; (3) self-criticism was a mediator between emotion regulation and disorder eating, which was significantly associated with LOC eating via increased negative urgency. Conclusion Our model shows that LOC eating occurs for individuals with the psychopathology of higher eating disorders who experience depressive symptoms and act rashly under distress for their inability to cope adequately with negative feelings of self-devaluation. These findings point to the importance of negative self-evaluations and feelings of inadequacy or worthlessness to understand LOC eating among college students.